Negative volatility spillovers in the unrestricted ECCC-GARCH model - Christian Conrad; Menelaos Karanasos (ETH Zurich, KOF Swiss Economic Institute, 2008)
This paper considers a formulation of the extended constant or time-varying conditional correlation GARCH model which allows for volatility feedback of either sign, i.e., positive or negative. In the previous literature, negative volatility spillovers were ruled out by the assumption that all the coefficients of the model are non-negative, which is a sufficient condition for ensuring the positive definiteness of the conditional covariance matrix. In order to allow for negative feedback, we show that the positive definiteness of the conditional covariance matrix can be guaranteed even if some of the parameters are negative. Thus, we extend the results of Nelson and Cao (1992) and Tsai and Chan (2008) to a multivariate setting. For the bivariate case of order one we look into the consequences of adopting these less severe restrictions and find that the flexibility of the process is substantially increased. Our results are helpful for the model-builder, who can consider the unrestricted formulation as a tool for testing various economic theories.
Keywords: C32; C51; C52; C53; 330; Inequality constraints; multivariate GARCH processes; volatility feedback; ARCH-Modell; Volatilität; Spillover-Effekt; Modell-Spezifikation; Theorie